2017
DOI: 10.7554/elife.25014
|View full text |Cite
|
Sign up to set email alerts
|

Meru couples planar cell polarity with apical-basal polarity during asymmetric cell division

Abstract: Polarity is a shared feature of most cells. In epithelia, apical-basal polarity often coexists, and sometimes intersects with planar cell polarity (PCP), which orients cells in the epithelial plane. From a limited set of core building blocks (e.g. the Par complexes for apical-basal polarity and the Frizzled/Dishevelled complex for PCP), a diverse array of polarized cells and tissues are generated. This suggests the existence of little-studied tissue-specific factors that rewire the core polarity modules to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…The meru gene was identified by Reeves and Posakony ( Reeves and Posakony 2005 ) as a direct target of the proneural genes and was implicated in the sensory perception of pain by ( Neely et al 2010 ). More recently, ( Banerjee et al 2017 ) have identified Meru as a modulator of cell polarity that connects planar cell polarity with apical-basal polarity during asymmetric cell divisions within the external sensory organ lineage. The identification of meru in the current screen points to a possible role of meru in the ChO lineage as well.…”
Section: Resultsmentioning
confidence: 99%
“…The meru gene was identified by Reeves and Posakony ( Reeves and Posakony 2005 ) as a direct target of the proneural genes and was implicated in the sensory perception of pain by ( Neely et al 2010 ). More recently, ( Banerjee et al 2017 ) have identified Meru as a modulator of cell polarity that connects planar cell polarity with apical-basal polarity during asymmetric cell divisions within the external sensory organ lineage. The identification of meru in the current screen points to a possible role of meru in the ChO lineage as well.…”
Section: Resultsmentioning
confidence: 99%
“…Temporal shifts in the behavior of polarity networks are widespread in developmental systems, as polarity components are rewired and repurposed in different cell types or through the cell cycle (e.g [49, 50, 51]). Mitotic entry directly regulates polarity network activity in many common models, including Drosophila neuroblasts [31, 32, 48] and S. cerevisiae [52, 53].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the mechanism responsible for this planar polarization is not known, the same biochemical or mechanical signals that affect core PCP proteins ( Chien et al, 2015 ; Chu and Sokol, 2016 ) ( Kim et al, 2018 ) are likely to regulate Par3. One possibility is that the association of core PCP protein complexes with Par3 may directly contribute to Par3 enrichment at specific locations ( Banerjee et al, 2017 ; Besson et al, 2015 ). In contrast to Xenopus Par3, fly Bazooka/Par3 is enriched at dorsoventral but not anteroposterior boundaries of intercalating cells during germ-band extension along the anteroposterior axis ( Simões et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bazooka/Par3 and its associated proteins have been functionally linked to PCP in specific Drosophila tissues ( Beati et al, 2018 ; Blankenship et al, 2006 ; Djiane et al, 2005 ; Harris and Peifer, 2007 ; Simões et al, 2010 ; Wasserscheid et al, 2007 ; Zallen and Wieschaus, 2004 ). Additionally, the effects of core PCP components on Par3 localization have been demonstrated in fly photoreceptor cells and sensor organ progenitors ( Aigouy and Le Bivic, 2016 ; Banerjee et al, 2017 ; Bellaïche et al, 2004 ; Besson et al, 2015 ). In vertebrates, a recent study also suggested a link between Par3 and PCP ( Lin and Yue, 2018 ), but whether Par3 itself is planar polarized, and how it modulates the activity of core PCP proteins has not been investigated.…”
Section: Introductionmentioning
confidence: 99%